Estimación de la socavación producida por el flujo de agua del Rio Martho al pie de estribos del Puente Sinsicap utilizando el programa hec – ras, Sinsicap – Provincia de Otuzco, 2019 - Gerónimo Polo, Miller Bain (2019)
In this research scour produced on the abutment's foot of the Sinsicap bridge due to the flow of Martho river, this estimation was made for different return periods, through a nonexperimental descriptive analysis for this reason a trip to the investigation zone was taken and was there where basic studies of engineering were developed. On one hand, one of these studies was the watershed topography, it was done with a 700-meters-upper-flow and 500-meters-downer-flow geometry and a 40-meters-width, also granulometry study of the riverbed, the left and rigth riverbank were done; on the other hand, metereologic datum of Sinsicap pluviometric station were downloaded from the SENAMHI website and with those the hydrological calculation of maximum rainfall and intensities was done, in addition to using engineering softwares (AutoCAD Civil 3D, Hidroesta, ArcGIS ang Google Earth) maximum flows for different return periods about 20, 50, 137 and 500 years were found; and of those the return period recommended was the 137-years-period registering a flow of 164.39 m3/s and the most critic return period was registered in 500 years with 207.12 m3/s. For the scour analysis on the abutments foot in Sinsicap bridge, HEC-RAS program was used and this program uses the Laursen's method for general contraction scour and the Froehlich's method for the local abutment scour analysis, for those result topographyc datum (D50), watershed parameters, topographic sections and maximum flows with different return periods ant the local scour in the abutments feet for a 137-years return period was 3.19 meters in the left abutment and 3.05 in the rigth one and for a 500-years return period was 4.05 in the left abutment and 3.84 in the rigth one and knowing the structure is a 10-years-bridge we induce that the bridge will be sustainable for 10 years more for this reason is recommended the protection through rock structures.